The impact of interventions to prevent truancy: A review of the research literature. (June 2020) - Keppens, Gil; Spruyt, Bram
Highlights: An original and critical review of current interventions to prevent truancy. Touches upon the theoretical frameworks that inform truancy interventions. Elaborates on implementation fidelity. Abstract: It is well established that truancy has a negative impact on pupils' educational careers. Much more discussion is needed concerning the strategies and interventions that effectively help to remedy truancy. Therefore, this article provides an integrative review of interventions to prevent truancy. Sixteen empirical studies that reported on the effectiveness of an intervention were coded according to the research design, participants, effect size, and outcomes. In addition, attention was paid to implementation fidelity and the theoretical frameworks that underpinned each intervention. The results indicate truant students benefit in particular from interventions that are derived from the school bonding perspective. In the conclusion we elaborate on the implications of our findings and discuss recommendations for practice, policy, and research.